SLIM’S STRUGGLE AGAINST DOMESTIC OPPRESSION IN ENOUGH THE MOVIE - MANGGIASIH, HANUM AYUNINGTYAS (Jurnal Ilmiah Mahasiswa FIB, 2014)
Women subordination phenomenon which puts women in limited roles creates a perspective that they cannot be equal to men. Most married women deal with the domestic sphere that their daily activities are maintaining household and serving the husband. In some cases, they experience domestic violence in the form of physical and psychological abuse. This phenomenon is represented by one of American movies entitled Enough which portrays a life of American woman named Slim whose husband is an abusive one. She has to experience several physical abuses and mental torment. The movie becomes the writer’s object of the study, focusing on the main character.This study uses feminism theory in relation to the knowledge about the inequal position between men and women in society. Besides, the information about domestic violence and woman struggle are also included as the supporting data.This study reveals that woman subordination phenomenon happens in Slim’s life after getting married. She has to face her fate as a housewife whose husband cheats and executes domestic violence. She experiences psychological abuse which results in depression and anxiety. Finally she struggles to end the violence and succeeds.The writer suggests the next researchers to conduct a comparative study on two movies which have the same domestic violence theme but from different cultural backgrounds because the difference of culture may lead into difference result.   Keywords: Feminist Literary Theory, Woman subordination, Woman Resistanceand Struggle, Domestic Violence, Movie.